2007
DOI: 10.4103/1463-1741.36981
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviour and noise exposure among adolescents

Abstract: Adolescents in Western society often expose themselves to high levels of sound in gyms, rock concerts, discotheques etc. As these behaviours are as threatening to young people's health as more traditional risk behaviours are, our aim in the present study was to analyze the relationship between self-exposure to noise, risk behaviours and risk judgements among 310 Swedish adolescents aged 15-20 (167 men; 143 women). Adolescents' behaviour in different traditional risk situations correlated with behaviour in nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 11 publications
4
57
2
7
Order By: Relevance
“…Various studies have shown that exposure to loud recreational music over prolonged periods of time leads to various effects on hearing and health [14][15][16][17][18][19]. These studies bought out recommendations for young people, who are perhaps not aware of the importance of good hearing to their future productivity and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that exposure to loud recreational music over prolonged periods of time leads to various effects on hearing and health [14][15][16][17][18][19]. These studies bought out recommendations for young people, who are perhaps not aware of the importance of good hearing to their future productivity and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Bohlin and Erlandsson [1] analyzed the relationship between self-exposure to noise, risk behaviors and risk judgments among 310 Swedish adolescents aged 15-20 (167 men, 143 women). Adolescents' behavior in different traditional risk situations correlated with behavior in noisy environments, while judgments about traditional risks correlated with judgments regarding noise exposure.…”
Section: Complaints Of the Studentsmentioning
confidence: 99%
“…These behaviors are as threatening to young people's health as more traditional risk behaviors [1]. It was reported that there would be an increase in high-tone hearing loss in USA among persons such as teenagers and young adults who were exposed to loud music [2].…”
Section: Introductionmentioning
confidence: 99%
“…There was also evidence that women are more risk-averse than men since they spent more decision time for the risky option, though they engage in risk behaviors at levels similar to men (Bohlin & Erlandsson, 2007;Van Leijenhorst et al, 2008).…”
Section: Discussionmentioning
confidence: 99%